Monetary Policy Transmission Channels and Economic Growth in Nigeria - Marshal, Iwedi (Asian Journal of Economics and Empirical Research, 2019)
This study empirically analyzes monetary policy transmission channels and economic growth in Nigeria using the vector auto regression model. Time series data were used for the period of 56 years (1960 to 2016) and sourced from the Central Bank of Nigeria statistical bulletin for various issues. The analyses show a good number of findings. Firstly, the unit root test results shows that all the variables of transmission channels are non-stationary at level, but appear stationary at first difference. Hence, the series are all integrated of order I (1). This of course authorized the study to proceed with the co-integration test which revealed that there is a long run relationship between monetary policy transmission channels and economic growth in Nigeria. Following the fact that the variables under study are co-integrated, the study went further to estimate the vector autoregressive model. The baseline result of the vector autoregressive model indicates that there exist a significant positive short run relationship between the channels of monetary policy transmission and macroeconomic output in Nigeria. Therefore, we conclude that interest rate and credit channels are critical channels for transmitting monetary policy impulses into the Nigeria economy. Based on this, the study recommends among others that the Nigeria monetary authority should as a matter of policy encourage and emphasize the good management of the transmission channels and this should be vigorously pursued, as it has the ability to trigger growth of the Nigeria economy.